O conceito de educação bilíngue sob a visão de Jim Cummins e Merill Swain: uma análise do livro “Bilinguismo na educação” - Tronco, Mariah Cruz de Souza (Universidade Federal de São Carlos, 2023)
This monograph presents the result of bibliographical research developed through content analysis of the book “Bilingualism in Education” (Cummins; Swain, 1986). Its general objective was to understand the concept of bilingual education in contemporary times from the perspective of Jim Cummins and Merrill Swain. Its specific objectives were: I. Identify the bilingual radical* in the work and the context units in which it is present; II. Recognize the authors' theoretical bases on which they support linguistic proficiency in the first and second language; III. Gather determining factors of bilingual education for academic success and failure. IV. Establish connections between the book's content and the reality of Brazilian bilingual education. Along the methodological path, an initial categorization of the record units identified was carried out based on the separation by sections of the book and, subsequently, a final categorization which gave rise to subcategories used as a basis for the author's inference. The theoretical framework was based on the Dialogic Education Model (Aubert et al, 2016), which highlights the transformative potential of education as an instrument for reducing social inequalities. As a result, a synthesis of the chapters and the categorization of registration units were carried out: I. Scientific research on bilingualism (characteristics and theoretical views); II. Benefits of bilingualism for cognition; III. Bilingualism and academic performance; IV. Dualities attributed to bilingualism V. Language proficiency (Testing and analysis) VI. Evaluation of bilinguals in standardized tests VII. Characteristics of bilingual programs. Furthermore, subcategories were created followed by an inference that related the following categories to the theoretical framework and the Brazilian scenario. The analysis concluded that additive bilingualism has advantages for cognitive and academic development and the existence of an urgency to end the stigmas that affect less socially privileged languages.

Esta monografía presenta los resultados de una investigación bibliográfica desarrollada a través del análisis de contenido del libro "Bilingüismo en la Educación" (Cummins; Swain, 1986). Su objetivo general fue comprender el concepto de educación bilingüe en la época contemporánea desde la perspectiva de Jim Cummins y Merrill Swain. Sus objetivos específicos fueron: I. Identificar la raíz bilingüe* en la obra y las unidades contextuales en las que está presente; II. Reconocer las bases teóricas de los autores sobre las cuales sustentan el dominio lingüístico en la primera y segunda lengua; III. Reunir los determinantes de la educación bilingüe para el éxito y el fracaso académico. IV. Establecer conexiones entre el contenido del libro y la realidad de la educación bilingüe brasileña. A lo largo del camino metodológico, se realizó una categorización inicial de las unidades de registro identificadas a partir de la separación por secciones del libro y, posteriormente, una categorización final que dio lugar a subcategorías que sirvieron de base para la inferencia del autor. El marco teórico se basó en el Modelo de Educación Dialógica (Aubert et al, 2016), que destaca el potencial transformador de la educación como instrumento para reducir las desigualdades sociales. Como resultado, se realizó una síntesis de los capítulos y la categorización de las unidades de registro: I. Investigación científica en bilingüismo (características y visiones teóricas); II. Beneficios del bilingüismo para la cognición; III. Bilingüismo y rendimiento académico; IV. Dualidades atribuidas al bilingüismo V. Competencia lingüística (Pruebas y análisis) VI. Evaluación de bilingües en pruebas estandarizadas VII. Características de los programas bilingües. Además, se crearon subcategorías seguidas de una inferencia que relacionó las siguientes categorías con el marco teórico y con el escenario brasileño. El análisis concluyó que el bilingüismo aditivo tiene ventajas para el desarrollo cognitivo y académico y la existencia de una urgencia por romper los estigmas que afectan a las lenguas menos privilegiadas socialmente.
The concept of bilingual education from the point of view of Jim Cummins and Merill Swain: an analysis of the book "Bilingualism in Education"
El concepto de educación bilingüe desde el punto de vista de Jim Cummins y Merill Swain: un análisis del libro "Bilingüismo en la Educación"
Keywords: Educação bilingue; Bilinguismo; Proficiência linguística; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM